Is Behaviourism Dead? Why Does This Matter (or Not Matter)? A Keynote Address - Marshall, Nancy (YU-WRITE: Journal of Graduate Student Research in Education, 2025)
I have been researching the impacts of behaviourism on the wellbeing of autistic and neurodivergent young people for several years now, and it has become the focus of my dissertation. The history of behaviourism is full of taboos and silenced narratives from all sides, making it an excellent topic for this year’s 20th Annual York University Graduate Student Conference in Education. It is an honour to be here.